UJI AKTIVITAS EKSTRAK ETANOL DAUN SIRIH CINA (Peperomia pellucida L.) TERHADAP BAKTERI Propionibacterium acnes - Maulana Zulkarnain Imansyah (Akademi Farmasi Yamasi Makassar, 2022)
Chinese betel leaf (Peperomia pellucida L.) has one of the benefits against Propionibacterium acnes bacteria which can overcome infectious diseases of the skin characterized by the formation of abscesses such as acne. This study aims to determine the activity of the ethanol extract of Chinese betel leaf (Peperomia pellucida L.) against Propionibacterium acnes bacteria.. Thiss researchh wass conducted in annexperimentali laboratory. Inntesting theeantibacterial inhibition with the diffusion method using Paper disk. The results obtained are inhibition zones around Paper disks with different diameters in each sample. The average inhibition diameter obtained from each sample of ethanol extract of Chinese betel leaf with a concentration of 5% is 6 mm, a concentration of 10% is 7.66 mm, and at a concentration of 15% is 12.33 mm.